2021
DOI: 10.1039/d1ra04298j
|View full text |Cite
|
Sign up to set email alerts
|

A label-free graphene-based impedimetric biosensor for real-time tracing of the cytokine storm in blood serum; suitable for screening COVID-19 patients

Abstract: Rapid and label-free detection of the cytokine storm in COVID-19 patients by an electrochemical impedimetric biosensor with a graphene working electrode.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 55 publications
0
5
0
Order By: Relevance
“…al. [ 229 ] developed an electrochemical biosensor for cytokine storm tracking in COVID-19 patients using graphene-modified copper electrodes and EIS. It must be clarified that they were not interested in specific biomarker detection (only 50%) but in indicating disease severity with biomarkers of inflammation in blood samples, so they did not use bioreceptors in the detection.…”
Section: Monitoring Signatures Of Biomarkers With Biosensors In the C...mentioning
confidence: 99%
“…al. [ 229 ] developed an electrochemical biosensor for cytokine storm tracking in COVID-19 patients using graphene-modified copper electrodes and EIS. It must be clarified that they were not interested in specific biomarker detection (only 50%) but in indicating disease severity with biomarkers of inflammation in blood samples, so they did not use bioreceptors in the detection.…”
Section: Monitoring Signatures Of Biomarkers With Biosensors In the C...mentioning
confidence: 99%
“…Graphene and its derivatives have been widely used as matrixes for the development of electrochemical biosensors [154][155][156][157][158][159] . Very recently, Khayamian et al 160 reported an impedimetric biosensor based on graphene for real-time monitoring the cytokine storm in serum which is suitable for screening COVID-19 patients. For this purpose, a graphene/copper working electrode on a sensor device was fabricated along with gold reference and gold electrodes.…”
Section: Nanostructuresmentioning
confidence: 99%
“…Recently, as the COVID-19 pandemic unfolded, multiple emerging techniques for fast, label-free, noninvasive screening methods were developed. [1][2][3][4][5][6][7] However, given the urgency of the need to screen large numbers of people, more established techniques-including reverse transcription polymerase chain reaction (RT-PCR)-were widely used for viral detection in blood, nasopharyngeal swaps, but also in saliva. [8][9][10] Despite being generally highly sensitive, techniques such as RT-PCR are often timeintensive and require costly chemical reagents.…”
Section: Introductionmentioning
confidence: 99%
“…Human biofluids are commonly used in screening, therapeutic and diagnostic applications as they enable the direct measurement of circulating biomarkers related to a patient's health. Recently, as the COVID‐19 pandemic unfolded, multiple emerging techniques for fast, label‐free, noninvasive screening methods were developed 1–7 . However, given the urgency of the need to screen large numbers of people, more established techniques–including reverse transcription polymerase chain reaction (RT‐PCR)–were widely used for viral detection in blood, nasopharyngeal swaps, but also in saliva 8–10 .…”
Section: Introductionmentioning
confidence: 99%